STUDIES ON FUCOIDAN AND ITS PRODUCTION FROM VIETNAMESE BROWN SEAWEEDS - Bui Minh Ly; Ngo Quoc Buu; Nguyen Duy Nhut; Pham Duc Thinh; Tran Thi Thanh Van (Universitas Gadjah Mada, 2005)
Sulfated fucans are among the most widely studied of all the sulfated polysaccharides of plant origin that exhibit biological activities in mammalian systems. In this report fucoidans from some Vietnamese Sargassumspecies such as S.polycystum, S.oligocystum, S.mcclurei, S. Swartzii and denticaprum were extracted and fractionated on a DEAE-Sephadex A-25 column. On the basis of chemical and spectral analyses, the fucoidan fractions obtained were found to be the sulfated fucogalactans containing sulfate ester groups and uronic acid, and composed essentially of fucose and galactose, as well as a minor amount of other sugars. The polysaccharide fractions were tested for anticancer activity. The primarily obtained results showed that all fucoidan fractions isolated from S. swartziidemonstrate bioactivity effects against cancer cells, while fraction F5 with a highest sulfate content exhibits the strongest anti-invasion activity. This indicates that sulfate content plays an important role in the anticancer activity of the brown algal fucoidans. A laboratory scale pilot for fuco idan production from Vietnamese brown seaweeds has been set with a capacity of 500 g of crude fucoidan per day.